Are Grasses Really Useful for the Phytoremediation of Potentially Toxic Trace Elements? A Review - Rabêlo, Flávio Henrique Silveira; Vangronsveld, Jaco; Baker, Alan J. M.; van der Ent, Antony; Alleoni, Luís Reynaldo Ferracciú (Frontiers in Plant Science, 2021)
Pollution of soil, water, and air by potentially toxic trace elements poses risks to environmental and human health. For this reason, many chemical, physical and biological processes of remediation have been developed to reduce (available) trace element concentrations in the environment. Among those technologies, phytoremediation is an environmentally friendly in situ and cost-effective approach to remediate sites with low-to-moderate pollution with trace elements. However, not all species have potential to be used for phytoremediation of trace element-polluted sites due to their morpho-physiological characteristics and low tolerance to toxicity induced by the trace elements. Grasses are prospective candidates due to their high biomass yields, fast growth, adaptations to infertile soils, and successive shoot regrowth after harvest. A large number of studies evaluating the processes related to uptake, transport, accumulation, and toxicity of trace element in grasses assessed for phytoremediation have been conducted. The aim of this review is (i) to syntheize the available information on the mechanisms involved in uptake, transport, accumulation, toxicity and tolerance to trace elements in grasses; (ii) to identify suitable grasses for trace elements phytoextraction, phytostabilization and phytofiltration; (iii) to describe the main strategies used to improve trace elements phytoremediation efficiency by grasses; and (iv) to point out the advantages, disadvantages and perspectives for the use of grasses for phytoremediation of trace element-polluted soils.